2009
DOI: 10.1055/s-0028-1100413
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Once-daily Sitagliptin on 24-h Glucose Control Following 4 Weeks of Treatment in Japanese Patients with Type 2 Diabetes Mellitus

Abstract: The aim of the study was to assess the efficacy/safety of once- (100 mg q.d.) or twice-daily (50 mg b.i.d.) sitagliptin 100 mg/day in Japanese patients with type 2 diabetes (T2DM). In this randomized, double-blind study, 80 patients with inadequate glycemic control (HbA1c=6.5-10%; FPG Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 6 publications
4
17
0
Order By: Relevance
“…[35][36][37][38][41][42][43][44][45]47,53 The low degree of Sitagliptin in the treatment of type 2 diabetes Dovepress submit your manuscript | www.dovepress.com Dovepress hypoglycemia is especially seen when compared with the risk of hypoglycemia during treatment with sulfonylurea ( Figure 4). This is explained by the glucose-dependency of the islet effects of GLP-1; hence when glucose levels are reduced the effects of GLP-1 in stimulating insulin secretion and inhibiting glucagon secretion vanish.…”
Section: Hypoglycemiamentioning
confidence: 99%
See 3 more Smart Citations
“…[35][36][37][38][41][42][43][44][45]47,53 The low degree of Sitagliptin in the treatment of type 2 diabetes Dovepress submit your manuscript | www.dovepress.com Dovepress hypoglycemia is especially seen when compared with the risk of hypoglycemia during treatment with sulfonylurea ( Figure 4). This is explained by the glucose-dependency of the islet effects of GLP-1; hence when glucose levels are reduced the effects of GLP-1 in stimulating insulin secretion and inhibiting glucagon secretion vanish.…”
Section: Hypoglycemiamentioning
confidence: 99%
“…[36][37][38][39][40][41][42][43][44][45][46] Improved β-cell function is also evident from reduced proinsulin to insulin ratio. 38,[41][42][43][44]47 Sitagliptin also reduces glucagon levels, 25,30 although this needs to be examined in more detail. The improved islet function by sitagliptin results in reduction of both fasting glucose and prandial glucose as revealed in different studies in subjects with type 2 diabetes.…”
Section: Mechanisms Of Actionmentioning
confidence: 99%
See 2 more Smart Citations
“…In 2009, the dipeptidyl peptidase-4 (DPP-4) inhibitor sitagliptin was approved as the first incretin enhancer for use in Japan [4][5][6][7][8][9][10][11] . Although it has been suggested that seasonal fluctuations of hemoglobin A1c (HbA1c) are noted in patients with type 2 diabetes, no reports have been published concerning the efficacy of antidiabetic agents for such fluctuations.…”
Section: Introductionmentioning
confidence: 99%